(untitled) (International Journal of Engineering and Computer Science, 2017)
The present paper extends the concepts of Torus Automorphism (TA) and Arnold Cat Map (ACM). The proposed Integrated Block based method uses Uniqueness Matrix (IBUM) for effective watermarking and a scrambled watermark is embedded robustly and imperceptibly. The proposed IBUM method efficiently made use of the earlier concepts TA and ACM effectively. TA disarranges the original image equally and randomly by maintaining high security over other methods. TA is a kinds of a dynamic system. After applying TA, the disarranged image is divided into 4×4 non overlapped blocks. On this, ACM is applied to shuffle the blocks. Then each 4×4 block is further divided into four 2×2 sub blocks and maintains hierarchical relationship. Each 2×2 sub block of the image represents a square matrix. Using Uniqueness Matrix (UM) the binary watermark is embedded in to the 2×2 sub blocks. This made the proposed system more secure and robust against several attacks. Based on TA and ACM the image is divided in to sub blocks with hierarchical nature. The characteristics of block based TA and ACM made the proposed system an excellent system, robust to many attacks, made complex in nature and impossible to predict over a long time. The proposed IBUM is tested with various attacks and compared with various existing image authentication and copyright protection methods. The comparisons and results indicate the efficacy of the proposed method over the existing methods.